The proper procedure on administrative seats, Lima 2012-2013 - Causillas-Aguilar, Celestino (2019)
The declaration and recognition of the rights and institutions in the various legal systems would have no reason to be regulated if they did not count with appropriate mechanisms to deal with the failure of compliance and / or violation of their content by different social agents. The ideal mechanism to enforce these rights and institutions and protect the rule of law and the Constitution, is the process through it seeks to protect the fundamental rights and the constitutionality rules and sanction same antisocial behavior is prevent the arbitrary exercise of power, are solved or prevent conflicts and legal uncertainty is removed . In this research analyze the right to due process, but in the field of administrative law, which will be called administrative due process, mainly regulated in paragraph 1.2 of Article IV of the Act No. 27444, General Administrative Procedure Act, where presumably due process is not regulated as a right in favor of the subjects administered within the administrative procedure, but as a set of safeguards for these during the course of the procedure. We can deduce that our legal premium guarantees respect for the Administration.